From Biopolitics to Biopoetics: a Hypothesis on the Relationship between Life and Writing - Yelin, Julieta Rebeca (2018)
The objective of this article is to examine the theoretical potential of the dialogues between literary critique and biopolitical thought, with an analysis centered on a reconsideration of the concept of interpretation. In order to accomplish this, we analyze the shift in Michel Foucault is thought around the beginning of the 1970s, a time during which the notion of life took prominence over the study of literature as a specific discipline. From this transformation, a particular way of approaching both literary and, generally speaking, artistic creations can be derived that would give rise to a biopoetics perspective.